Systematic Review of Deep Learning in Primary Education : Ulasan Sistematis tentang Deep Learning dalam Pendidikan Dasar - Adi Putra, Deni (Universitas Muhammadiyah Sidoarjo, 2026)
This review study analyzes the integration of deep learning concepts into elementary school curriculum learning. The aim of this study is to identify strategies and solutions for practical purposes in integrating deep learning concepts into the curriculum. To achieve this goal, researchers analyzed 30 literatures from 2020 to 2025. These literatures were analyzed from the perspective of curriculum, methods, learning outcomes, and potential implementation obstacles. Project-based learning methods and group collaboration are preferred and can improve students' understanding of deep learning, according to the study's findings. This study also offers various recommendations to overcome obstacles in integrating deep learning. These recommendations include teacher support (disposition) and commitment to teaching new concepts and adequate school facilities. This study also proposes the development of a more flexible (modular) curriculum and the placement of devices for children's purposes, as well as interdisciplinary collaboration. Highlights: Project-based and collaborative learning approaches are most frequently associated with improved student understanding and engagement. Curriculum alignment with cognitive development stages is a recurring requirement across successful implementations. Ethical considerations, teacher preparedness, and resource limitations remain persistent challenges in elementary contexts. Keywords: Deep Learning, Elementary School Curriculum, Artificial Intelligence, AI Literacy, STEM Education